INTEGRATION OF DEDUCTIVE AND INDUCTIVE APPROACHES TO TEACHING B1 LEARNERS’ GRAMMAR (Conference Zone, 2022)
Our research concerns with mixing the two given approaches in a way that maximizes students’ understanding of the subject. We tested a new way in which the classes are taught with 3 separate scenarios: inductive only, deductive only, and combined one. The study also includes trying out both of these methods for each grammatic rule individually, to see which one is perceived best among students. Surveys had been done before and those surveys had put emphasis on identifying the best ways to improve the overall effectiveness of the topic delivered to pupils. Likewise, our undertakings also serve for creating an innovative way to ease and simplify the learning process